Association between a heme oxygenase-2 genetic variant and risk of Parkinson's disease in Han Chinese. (6th March 2017) - Tian, Sijia; Yang, Xinglong; Zhao, Quanzhen; Zheng, Jinhua; Huang, Hongyan; Chen, Yalan; An, Ran; Xu, Yanming
Highlights: We assessed the association between three heme oxygenase genetic variants and sporadic Parkinson's disease. 583 Chinese Han patients with sporadic Parkinson's disease were genotyped. Our data suggest that rs1051308 is related to the risk of Parkinson's disease in Han Chinese. Abstract: Studies have reported conflicting results about possible associations between variants in heme oxygenase ( HMOX ) genes and risk of Parkinson's disease (PD) in Caucasians, and little is known about these associations in Asians. We genotyped the single-nucleotide polymorphisms (SNPs) rs2071746 and rs2071747 in HMOX1 and rs1051308 in HMOX2 in 583 Han Chinese with PD and 627 healthy controls using a customized 2 × 48-Plex SNP Scan™ kit. Frequencies of genotypes and minor alleles were similar between patients and controls for rs2071746 and rs2071747, but different for rs1051308( P = 0.004, OR 1.705, 95%CI 1.191–2.442 for genotypes; P = 0.009, OR 1.249, 95%CI 1.037–1.476 for alleles). Our results suggest that rs1051308 is associated with risk of developing PD in Han Chinese, and further studies involving various ethnicities are needed to validate the association.